Synergistic interfacial effect of polymer stabilized graphene via non-covalent functionalization in poly(vinylidene fluoride) matrix yielding superior mechanical and electronic properties. (6th April 2016) - Maity, Nirmal; Mandal, Amit; Nandi, Arun K.
Abstract: Polythiophene- graft -poly(methyl methacrylate) (PT- g -PMMA) functionalized non-covalently with reduced graphene oxide(RGO) (PFG) is used to make composites with poly(vinylidene fluoride) (PVDF), designated as PRPx where x represents PFG content(wt%). RGOs are distributed homogenously in PVDF matrix. FTIR spectra indicate 90% piezoelectric β-polymorph in PRP5. Thermal studies exhibit small decrease of PVDF crystallinity, accelerated crystallization, and enhanced thermal stability. Increase in glass transition and other relaxation temperatures and a maximum (60%) increase of storage modulus are noticed. PRP1 exhibits increment of tensile strength and strain of 317% and 302% over PVDF. Young's modulus varies with PFG following Halpin–Tsai equation for random distribution. The dc-conductivity exhibits percolation threshold at 0.24 vol% PFG with maximum conductivity of 7 × 10 −3 Scm −1 . The dielectric permittivity also exhibits sharp increase with a maximum of 446.0 at 10 2 Hz for PRP5. A comparison of the present data with other PVDF composites with covalently functionalized RGO dictates its supremacy. Graphical abstract: Highlights: Non-covalent functionalization of RGO with PT-g-PMMA to make composite with PVDF. 90% ß-phase formation of PVDF in 5% filler concentration. 1% filler concentration exhibits tensile strength & strain increment 317% & 302%. Percolation threshold 0.24% filler concentration with highest conductivity7ms/cm. Non-covalently functionalized RGO shows highest reinforcement and conductivity.